Sultan Baharuddin Harahap: Kiprahnya dalam Pengembangan Pendidikan Islam di Kabupaten Tapanuli Selatan - HTS, Wike Wijayanti; Hanum, Azizah; Arsyad, Junaidi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The purposes of this research is to obtain the biography, contributions and progress of Sultan Baharuddin Harahap in South Tapanuli. The research method used is qualitative research with a character study approach. This writing was produced by collecting data obtained by reading references through articles, journals, books, then approaching the family, loyal bodyguards of Sultan Baharuddin Harahap, friends of Sultan Baharuddin Harahap's wife, and heads/managers of educational institutions left behind by the Sultan. Baharuddin Harahap. The results of the research show that Sultan Baharuddin Harahap is a famous king in South Tapanuli Regency who has the title